Pengaruh Penambahan Pupuk Urea Dan Fly Ash Dengan Variasi Pemeraman Pada Tanah Lempung Terhadap Nilai Cbr Dan Permeabilitas - Ical Mahenra S; Syahrul Sariman; Arman Setiawan (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Soil is the most important part to support a construction, one of which is clay soil which has a high moisture content so that the CBR of clay soil is low and causes a decrease in soil carrying capacity. This study aims to determine the effect of the addition of urea and fly ash fertilizers on the CBR value and permeability of clay soil. The percentages used in this study are Fly Ash 10% and Urea Fertilizer 10% and 20% plus variations in curing time, namely 7 and 14 days. According to AASHTO, soil is included in the A-7-5 category while according to USCS soil is included in the CH category. The maximum CBR value occurred at the addition of 10% Fly Ash + 20% Urea Fertilizer with 14 days of Curing with a CBR value of 23.89%.while the maximum Permeability Value occurred at the addition of 10% Fly Ash + 20% Urea Fertilizer with 14 days of Curing with a Coefficient value of 0.0151 cm/minute.